Analysis of e-learning problems during covid-19 pandemic - Duha Hardiyanti Awalia; Dadi Setiadi; Kusmiyati Kusmiyati (Jurnal Pijar Mipa, 2021)
The occurrence of the Covid-19 outbreak requires the implementation of distance learning by implementing a learning system such as e-learning. There must be problems during the learning process using e-learning. The purpose of the research is to describe the difficulties of e-learning during the Covid-19 pandemic for class X students at SMAN 1 Keruak. The population in this study was all students in the class of X IPA SMAN 1 Keruak, divided into four courses with 120 people. The sample was taken randomly. The research method used is a descriptive research method with a qualitative approach. The research results in e-learning were carried out in 3 stages, namely learning planning, learning process, and evaluation. Students experienced difficulties in the e-learning learning process during the Covid-19 pandemic regarding the readiness of educational institutions, internet connection, internet packages, inadequate devices, and obstacles to understanding the material. During implementing e-learning, students experienced difficulties with the highest percentage of 78%. Based on these results, it can be stated that students experienced difficulties in the e-learning process during the Covid-19 pandemic regarding facilities and infrastructure.